2011
DOI: 10.5194/angeo-29-865-2011
|View full text |Cite
|
Sign up to set email alerts
|

Annual and semiannual variations of vertical total electron content during high solar activity based on GPS observations

Abstract: Abstract. Annual, semiannual and seasonal variations of the Vertical Total Electron Content (VTEC) have been investigated during high solar activity in 2000. In this work we use Global IGS VTEC maps and Principal Component Analysis to study spatial and temporal ionospheric variability. The behavior of VTEC variations at two-hour periods, at noon and at night is analyzed. Particular characteristics associated with each period and the geomagnetic regions are highlighted.The variations at night are smaller than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
3
20
1
Order By: Relevance
“…Further, we observed opposite latitudinal asymmetry among annual and semiannual variations for three GNSS stations. Zhao et al (2008) and Natali and Meza (2011) also reported the similar findings for high solar activity year. The results in Table 2 and " Fig.…”
Section: Resultssupporting
confidence: 72%
“…Further, we observed opposite latitudinal asymmetry among annual and semiannual variations for three GNSS stations. Zhao et al (2008) and Natali and Meza (2011) also reported the similar findings for high solar activity year. The results in Table 2 and " Fig.…”
Section: Resultssupporting
confidence: 72%
“…[7 and 9] both worked on TEC at stations (Ilorin, Nigeria and India) in low latitudes during the low solar activity period, and they showed that the diurnal characteristics of TEC depend on season, solar activity, geomagnetic activity, and latitude. [7, 8 and 13] showed that the seasonal variations in vertical TEC are higher during the equinox than the solstice during low solar activity, while [14] showed that the story was the same at high solar activity using different stations. Quantitative study of transient variations in GPS TEC, involving simultaneously measured data from multiple stations in Nigeria, to show the diurnal and the seasonal variation of the GPS-TEC data has been done by several authors: [9, 10, 15 -17].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is a lack of information for the longitudinal variations of the neutral density of N2 during nighttime. A few studies revealed that the annual and semiannual variations of the nighttime electron density are absent at midlatitudes in both hemispheres (e.g., Ma et al, 2003;Natali and Meza, 2011), which suggests the neutral composition may have a lesser effect on the ionospheric electron density longitudinal pattern during nighttime than it has during daytime. In the present study, the maximum relative longitudinal difference occurs around midnight in summer, which is associated with the occurrence time of maximum upward plasma drifts.…”
Section: The Wsa and The Electron Density Longitudinal Differencementioning
confidence: 99%